Pengaruh Beban Pendinginan Terhadap Temperatur Sistem Pengkondisian udara Hibrida Dengan Kondensor Dummy Tipe Trombone Coil Menggunakan Pipa Tembaga Berdiameter 1/4" Sebagai Water Heater - Renaldi Khaesar Kumara; Azridjal Aziz; Rahmat Iman Mainil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The hybrid air conditioning systems can improve the energy efficiency by recovering waste heat of condenser that can be useful for various purposes. There are many experimental studies about this system which aimed to investigate and improve the energy efficiency. This experimental study aims to investigate the effect of cooling loads to system temperatures of hybrid air conditioning with trombone coil type of dummy condenser using 1/4″ diameter of copper pipe as water heater. The system has been tested with several cooling loads as residential cooling load simulation, such as 0 Watt, 1000 Watt, 2000 Watt, and 3000 Watt. The result shows that the maximum water temperature is obtained at 47.30 ˚C with average discharge temperature of 105.45 ˚C in 3000 Watt cooling load after 120 minutes of operation. The more the cooling load applied to simulation room, the more the temperatures of water and discharge increased.Keywords: hybrid air conditioning system, dummy condenser, trombone coil, water heater.